Florida's Introduced Birds: House Finch (Carpodacus mexicanus) - Steve A. Johnson; Jill Sox (EDIS)
WEC-253, a 5-page illustrated fact sheet by Steve A. Johnson and Jill Sox, introduces this small, seed-eating songbird native to the southwestern United States, but whose range has extended to northern parts of Florida since the 1950s. Includes online guides, books, and other publications that provide additional information on Florida's native and non-native birds. Published by the UF Department of Wildlife Ecology and Conservation, March 2009.